Rumanian Folk Music - Bartok, Bela. author. aut Link
787 p.
Keywords: he editorial treatment of the second volume of Bela Bart6k's T Rumanian Folk Music is not dissimilar to that applied to Vol. I. The matter of poetic texts here, however, must allow for a sizeable increase in corrigenda and addenda. But first, let us delve into the source material upon which Vol. II is based. THE MANUSCRIPTS The various drafts of Vol. II fall into five basic categories of editorial process: music, texts, notes to the melodies (and texts), preface, and 1 miscellaneous reference material. M usic.-The first draft comprises field recording transcriptions, and notations made on the spot when recording was not possible. Bart6k left behind the bulk of this material when he emigrated to the United States in October, 1940 (The complete poetic text appears together with the music in each transcription).2 The second draft, uncorrected, comprises 304 pages printed by photo 3 offset process from master sheets. The third draft, reproduced from 667 pages of master sheets, is 1 All are contained in the New York Bartok Archives (hereinafter referred to as the BA) in envelopes designated by the author as Nos. 82-83, 85-86, 88, 90-97, 100, 102, and 106-107. See fn. 12 of the editorial Preface to Vol. I for the complete listing of the Rumanian folk' music MS.